Pedagogical experiences of Elementary and middle school teachers during the Covid-19 pandemic confinement - Salamanca, Mónica (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This phenomenological research aimed to analyse the pedagogical experiences of a group of primary and secondary school teachers in the municipality of Villa de Leyva, Colombia, along the confinement period due to the Covid-19 pandemic. It explored, through semi-structured interviews to 10 teachers, topics such as the online teaching adaptation, technological challenges, digital divide, learning assessment and the teacher’s well-being. The results found that the teacher’s training was insufficient, the educational inequality exacerbated by the lack of internet access and digital devices. The learning assessment and measuring was made difficult, as it was maintaining the attention and participation of the students as well. In addition, teachers faced work overload and physical and mental health problems. The discussion highlights the importance of an integral teacher’s training for an effective integration of technology in teaching, also the need for a technological access and teacher’s well-being equality. In conclusion, it has been emphasised learning of this experience for future educative transformations, prioritising the inclusion of technology, equity, and well-being.